2021
DOI: 10.1590/1981-6723.24720
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional quality and sensory acceptance of biofortified cassava

Abstract: It is estimated that the global number of people affected by micronutrient deficiency, known worldwide as hidden hunger, is over two billion and also considered a public health problem. Therefore, this study aimed to evaluate biofortified cassava cultivars in relation to their physical-chemical composition, total carotenoids and to verify their sensory acceptance by schoolchildren. The study was conducted in Santa Maria, in the state of Rio Grande do Sul (RS), Brazil, with four cassava cultivars, two biofortif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Consequently, investigations centered on enhancing the nutritional profile of cassava roots can contribute to the development of effective techniques for the biofortification of cassava. Tagliapietra [49], in their study on the nutritional quality and sensory acceptance of biofortified cassava, found higher levels of carotenoids in the biofortified cultivars. Additionally, the sensory analysis achieved an approval rate of 78.7%, demonstrating good potential for incorporating these roots into school meals.…”
Section: Discussionmentioning
confidence: 97%
“…Consequently, investigations centered on enhancing the nutritional profile of cassava roots can contribute to the development of effective techniques for the biofortification of cassava. Tagliapietra [49], in their study on the nutritional quality and sensory acceptance of biofortified cassava, found higher levels of carotenoids in the biofortified cultivars. Additionally, the sensory analysis achieved an approval rate of 78.7%, demonstrating good potential for incorporating these roots into school meals.…”
Section: Discussionmentioning
confidence: 97%
“…Cassava (Manihot esculenta Crantz) is considered a very important crop in tropical and subtropical countries as a starch source (Da Costa Nunes et al, 2021), as it is adapted to soils with low nutrient availability and drought tolerance (Tagliapietra;Zanon;Fernandes, 2021); in addition, it has become the third leading calorie source after rice and corn (excluding sugarcane) for vulnerable populations in Africa, Asia, and South America, and its use in the food and nonfood industries is growing (Versino;Urriza;García, 2019). It is increasingly suited to modern agriculture and competes with cereals such as rice (Jeong;Lee;Chung, 2021) and wheat (Tao et al, 2021), which have been further investigated seeking to improve its production and processing.…”
Section: Introductionmentioning
confidence: 99%